Allopurinol use and risk of acute coronary syndrome in gout patients: a population-based cohort study in Sweden - Ulf Lindström; Lennart Jacobsson; Mats Dehlin; Karin Bengtsson; Panagiota Drivelegka; Tatiana Zverkova Sandström (BMJ Open)
Objectives To investigate the impact of allopurinol use on the risk of first-ever acute coronary syndrome (ACS) event in patients with gout.Methods Using national and regional register data, we included all patients with a gout diagnosis at primary or specialised care in Western Sweden in the period 2007–2017 (n=18 862; 67% male patients). Patients with a prior history of coronary heart disease (CHD) were excluded. Follow-up started at the first gout diagnosis and ended at the first-ever ACS event, death or study end. The main outcome was the risk of first-ever ACS in: (1) allopurinol users versus non-users, by defining three categories of allopurinol exposure: exposed to 100 mg, >100 mg and no exposure (reference) and (2) allopurinol initiators (within 125 days) versus long-term users (reference). Multivariable logistic regression analysis was used to calculate ORs and 95% CIs.Results In analysis 1 (n=18 862), 15.3% (n=2892) were exposed to 100 mg, 9.1% (n=1717) to >100 mg and 75.6% (n=14 253) were not exposed. Allopurinol users were older and had more comorbidities compared with non-users. Allopurinol exposure (100 mg and >100 mg) was associated with significantly lower odds of first-ever ACS (OR 0.77; 95% CI 0.63 to 0.94, and OR 0.61; 95% CI 0.47 to 0.81, respectively). In Analysis 2, allopurinol initiators (n=489) had significantly higher odds of first-ever ACS compared with long-term users (n=2916) (OR 1.68; 95% CI 1.03 to 2.75).Conclusions In patients with gout and without CHD, long-term allopurinol use protects against first-ever ACS compared with non-users. In contrast, allopurinol initiators, possibly having more systemic inflammation, had a higher risk of first-ever ACS compared with long-term users.